A bio-bibliography of Claro Mayo Recto - Torres, Trinidad P. (Institute of Library Science, University of the Philippines Diliman, 1967)
Claro Mayo Recto, a great Filipino statesman, wrote a number of literary and nonliterary works which have been immortal because of the great ideas they contain. Through his works, biographers can have an insight into the character and personality of this man and see the role he played in the realm of Philippine politics.